Renovation of the Environmental Education Camp “Ecologist” - Goroshkina, Sofia; Druzhinina, Inna (project baikal, 2022)
Renovation of the environmental education camp in Listvyanka settlement opens up prospects for the development of children’s, family inclusive recreation and can have a positive effect on the region’s economy as a whole. Creating a comfortable modern environment for children is based on studying the territory, structuring and developing the existing functional zones. There is an emphasis on renewing the image of the entire complex of buildings.